The Effect Of Leaflet-Based Health Education On Breastfeeding On Increasing Knowledge - Dewi Parwati; Norma Safitri; Musdalifah Musdalifah (Green Health International Journal of Health Sciences Nursing and Nutrition, 2025)
Breast Self-Examination (BSE) is an important action in the early detection of breast cancer. Early detection plays a crucial role in increasing the success rate of treatment and reducing mortality from breast cancer. This study aims to determine the effect of leaflet-based health education about BSE on increasing knowledge among Women of Childbearing Age in the Tarailu Health Center Work Area, Mamuju Regency. The research method used is quantitative research with a Quasi-Experimental research design and a "One Group Pretest-Posttest" design using a purposive sampling technique with a sample of 40 respondents. The results of the study show a significant increase in the respondents' knowledge after being given leaflet-based health education about BSE. Based on the paired sample t-test, a T value of -5.182 was obtained with a p-value of 0.00 < 0.005. This indicates that the hypothesis is accepted, meaning there is an effect of health education about BSE on increasing knowledge among Women of Childbearing Age in the Tarailu Health Center Work Area, Mamuju Regency, in 2024. This study provides useful information to raise awareness about the importance of breast self-examination as an early detection step for breast cancer among women of childbearing age in the area.